Potensi dan Masalah Destinasi Pariwisata Replika di Daerah Istimewa Yogyakarta - Amalia Deandra Ristinanda; Wiendu Nuryanti (ATRIUM: Jurnal Arsitektur, 2021)
Title: Potential and Problem of Replica Tourism Destinations in Special District of Yogyakarta   Special Region of Yogyakarta is the tourism assets so it has the potential of tourism destinations to grow. The replica tourism destinations grow in contrast to the culture owned by the regions and the community. It is essential to see the condition and the development of the replica tourism destinations, their potentials, their problems and their opportunities as the driving force of tourism distribution. The method used in this research is directive interview. The overall result shown that the condition and the development is unstable, there was a leap of the tourist numbers but then decreasing. The involvement of local community and the increasing of tourism diversity became the potential of these destinations, but they had the problem of being sustainable. The replica tourism destinations grew due to the existence of tourists’ interests and they gave benefit to the local community but as time goes by, they were left since they were temporary.